VCE further mathematics units 3 & 4 (Victorian Certificate of Education Maths)
This CD-ROM is for students studying VCE General Mathematics. For every topic the basic theory and formulae are explained with examples plus multiple choice exercises. Four challenge questions are provided for each topic with multiple choice solution paths. Each student has his/her own logon and password and progress scores are held on the hard disk. On completion of the CD each student is presented with a certificate of achievement detailing percentage scores and grades by topic. Topics covered in this CD : data analysis 1, data analysis 2, data analysis 3, arithmetic, probability and statistics, geometry and trigonometry, graphs and relations, business-related maths and networks and decision maths.